Oxytocin in the Treatment of Psychiatric Disorders - Salim Cagatay KAGIZMAN; Cicek HOCAOGLU (Medeniyet Medical Journal)
Oxytocin is a peptide hormone that is most known for its role in reproduction. However, many effects other than reproduction have been defined. The lifetime prevalence of mental disorders is approximately 20%, and they have a significant ratio among the diseases that lead to disability. Treatment resistance may cause the mental disorder to become chronic and increase disability. With the examination of the oxytocinergic system, both the elucidation of the etiology of the diseases and their evaluation as a new treatment option have come to the fore. In various studies, it has been desired to create a more effective treatment model by measuring the level of oxytocin in psychiatric disorders, examining its receptor, and applying exogenous oxytocin in the treatment. In this review, an overview of oxytocin's efficacy in treatment is presented by considering the relationship between psychiatric disorders and the oxytocinergic system.